Implementation of AI-Based Video Media Assisted Discovery Learning Model to Improve Science Learning Results of Grade V Students State Elementary School 8 Laiya Island - Fadila, Nurul; Irfan, Muhammad; Syawaluddin, Ahmad (Program Studi PGSD FIP UNM, 2024)
This study is motivated by low student learning outcomes in the implementation of learning in class IV in science learning at SDN 8 Laiya Island. The objectives of this study are (1) to see how the learning process by applying the discovery learning model assisted by AI-based video media (2) to determine the improvement of learning outcomes of grade V students of State Elementary School 8 Laiya Island through the application of the discovery learning model assisted by AI-based video media. This study used a qualitative descriptive approach with a Classroom Action Research (PTK) design. The subjects of this study were all grade V students of SDN 8 Laiya Island, totaling 13 people. The implementation of the research was carried out for two cycles. Each cycle consists of planning, implementation, observation and reflection stages of the follow-up plan. Data was collected using observation, tests, and documentation. In cycle I, the results of research on the learning process in teacher activities and student activities were in the good category and in cycle II the learning process in teacher and student activities was in the very good category. The results showed a significant increase in learning outcomes in each cycle. In cycle I student learning outcomes were still low while in cycle II the learning outcomes showed a fairly high increase. Thus it can be concluded that the application of the discovery learning model assisted by med.Keywords: Discovery Learning, Video Media, Learning Outcomes